Acute Medicine: A New Horizon - Ahmad, J; Nizhu, L; Haroon , MA; Anam , AM (Bangladesh Journal of Medicine, 2023)
Background: Acute medicine is concerned with the immediate and early management of adult patients suffering from a wide range of medical conditions requiring urgent care. It is a new concept in the context of our country. Given the current situation of the burden of patients against available resources, management of acute conditions under the umbrella of acute medicine may have a promising result. Methods: All the information was collected from the department of Acute Medicine of Square Hospitals Limited since it started its journey on the 15th October, 2022. Data of first 175 days (15th October, 2022 to 7th April, 2023) were compiled and the outcome was observed. Results: Among 615 patients of department of Acute Medicine, 50% were male and 50% were female. Among them 84% were managed within 72 hours; 92.4% improved and 7.2% needed treatment escalation. Among the patients who got improved, 76% were shifted to cabin and 13% were discharged home after management of acute condition. Conclusion: The observation revealed better patient outcome with less hospital stay. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 218